2012
DOI: 10.1017/s0959774312000467
|View full text |Cite
|
Sign up to set email alerts
|

Civic and Household Community Relationships at Teotihuacan, Mexico: a Space Syntax Approach

Abstract: It is held that the study of complex societies can effectively focus on the human interactions that define communities. Given the operational primacy of architectural survey in archaeological investigations, with some prominent exceptions, it is surprising how little attention has been paid to how communities of varying scales can actually be identified using these data sets. This article weds a modified version of Yaeger and Canuto's (2000) ‘interactional approach’ to community identity with a materialist (em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 39 publications
(52 reference statements)
1
9
0
1
Order By: Relevance
“…This is consistent with the hypothesis that the designs of the city’s prominent religious structures, namely the Three-Temple Compound and talud-tablero architecture, first originated in a domestic context [32] , indicating that there was no clear distinction between sacred and mundane spaces. It also matches the findings of a space syntax analysis of the ceremonial core and of several apartment compounds, which suggest that the community structure of the apartment compounds and the city’s organization at the larger civic scale reflect each other [46] . Moreover, it was found that, contrary to traditional assumptions about the grid-like regularity of Teotihuacan’s layout, most of its streets are in reality short and discontinuous rather than long and straight, and the actual layout therefore does not fit with expectations of having been designed by one centralized authority.…”
Section: Introductionsupporting
confidence: 79%
“…This is consistent with the hypothesis that the designs of the city’s prominent religious structures, namely the Three-Temple Compound and talud-tablero architecture, first originated in a domestic context [32] , indicating that there was no clear distinction between sacred and mundane spaces. It also matches the findings of a space syntax analysis of the ceremonial core and of several apartment compounds, which suggest that the community structure of the apartment compounds and the city’s organization at the larger civic scale reflect each other [46] . Moreover, it was found that, contrary to traditional assumptions about the grid-like regularity of Teotihuacan’s layout, most of its streets are in reality short and discontinuous rather than long and straight, and the actual layout therefore does not fit with expectations of having been designed by one centralized authority.…”
Section: Introductionsupporting
confidence: 79%
“…Space syntax analysis of path structure Hillier and Hanson's (1984) use of space syntax analysis to understand the social logic of space provides an appropriate method for the identification of structurally central and integrated areas within the settlement of Yanawilka (cf. Hanson 1998;DeMarrais 2001;Morton et al 2012). A comparison of the connectivity and integration of paths of movement and lines of visibility, and their proximity to certain architectural and public spaces, may reveal important aspects of community organisation.…”
Section: Archaeological Research On Mitmaqkuna Settlementsmentioning
confidence: 99%
“…Using the methods of space syntax, we can explore that possibility. Originally developed by architects as a quantitative tool to understand how the design of buildings and cities impact human interaction (Hillier and Hanson 1984), space syntax has been applied by numerous archaeologists working throughout the world to explore the ways social organization is reflected in architecture (e.g., Blanton 1994;Cutting 2003;Dawson 2002;Edwards 2013;Funari and Zarankin 2003;Jamieson 2000;Morton et al 2012;Robb 2007;Smith 2007;Wernke 2012). Space syntax is essentially structuralist; the methodology assumes that the ways people move through space impacts their behavior, consciously and unconsciously (Cutting 2003: 3).…”
Section: The Syntax Of Acocotla's Cascomentioning
confidence: 99%